Pengembangan Media Animasi Berbasis Pendidikan Karakter Materi Mendongeng - Sukma Sukma; Donna Rhamdan (Justek : Jurnal Sains dan Teknologi, 2025)
This study aims to develop Character Educatoin-Based Animated Media (CEBAM) for storytelling materials in Grade III at SDN 023 Tarakan. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments included observation, interviews, validation sheets, student interest questionnaires, and documentation. The documentation in this developmental study included student activities during the trial implementation of the CEBAM learning media. The validation results showed that the media expert provided a score of 89%, the language expert gave 86,6%, and the practitioner provided 94,4%-all categorized as “highly feasible”. During the limited trial, the student interest score reached 90,3%, and in the field trial, it was 92,1%-both categorized as “very interesting”. Based on these validation and trial results, the CEBAM for storytelling material in grade III at SDN 023 Tarakan is considered highly suitable for use in the learning process. Furthermore, the student interest responses confirm that the CEBAM is highly engaging for classroom use.